Iron Accumulation Is Not Homogenous among Patients with Parkinson’s Disease - Khashayar Dashtipour; Manju Liu; Camellia Kani; Pejman Dalaie; Andre Obenaus; Daniel Simmons; Nicole M. Gatto; Mehran Zarifi (Parkinson's Disease)
Background. Iron is considered to lead to neurodegeneration and has been hypothesized as a possible cause of Parkinson’s disease (PD). Susceptibility-weighted imaging (SWI) is a powerful tool to measure phase related iron content of brain. Methods. Twelve de novo patients with PD were recruited from the Movement Disorders Clinic, Department of Neurology, Loma Linda University. Twelve age- and sex-matched non-PD subjects were recruited from neurology clinic as controls. Using SWI, the phase related iron content was estimated from different brain regions of interest (ROIs). Results. There was a trend between increasing age and iron accumulation in the globus pallidus and putamen in all subjects. Iron accumulation was not significant in different ROIs in PD patients compared to controls after adjustment for age. Our data revealed heterogeneity of phase values in different brain ROIs among all subjects with an exaggerated trend at SN in PD patients. Conclusions. Our data suggest a nonhomogeneous pattern of iron accumulation in different brain regions among PD patients. Further studies are needed to explore whether this may correlate to the progression of PD. To our knowledge, this is the first study demonstrating the heterogeneity of iron accumulation in the brain, among patients with PD.